PENGARUH PEMBIASAAN SHALAT BERJAMAAH TERHADAP KEDISIPLINAN PESERTA DIDIK KELAS IX SMP NEGERI 12 MAKASSAR - Widya, Said Syarifuddin Abu Baedah; Abdul Wahab , Andi Bunyamin , Mustamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of congregational prayer habits on the discipline of grade IX students at SMP Negeri 12 Makassar. The research method used is quantitative with data analysis in the form of percentages and hypothesis testing. The results of the study showed that the habit of congregational prayer through routine and spontaneous activities is in the moderate category, with percentages of 74.03% and 64.43% respectively. In addition, student discipline is also in the moderate category with a percentage of 40.26% in the moderate category. The test shows that the variable of congregational prayer habits has a significant effect on student discipline, with a significance value of 0.001 (p <0.05). Meanwhile, certain variables do not show a significant effect. The results of the determination coefficient test show that 61.3% of student discipline is influenced by the habit of congregational prayer, while 38.7% is influenced by other factors. Overall, this study shows that there is a strong influence between the habit of praying in congregation and student discipline at SMP Negeri 12 Makassar, which shows the importance of religious practices in forming students' disciplined character. Keywords: Congregational Prayer, Discipline, Students